The Impact of Reading English Academic Articles in the Development of Vocabulary Among EFL Student’s - Aulia Safitri; Sandrina Rizkia Ramadhani; Novi Rahmadaniati; Abdul Syahid (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This study examines the relationship between vocabulary learning strategies and vocabulary size among EFL students, focusing on the impact of reading English academic articles. Using a quantitative approach with a correlational descriptive design, this research involved EFL students at IAIN Palangka Raya. Participants completed two instruments: Schmitt’s (2000) Vocabulary Learning Strategies Questionnaire (VLSQ) to identify the strategies students use, and Beglar and Nation’s (2013) Vocabulary Size Test (VST) to measure vocabulary knowledge. The results indicate that reading English academic articles positively influences vocabulary development, particularly in acquiring high and medium-frequency words with an average of 78/100. Social Strategy emerged as the most widely used approach, followed by Determination and Metacognitive Strategies. These strategies help students understand new vocabulary through discussions with peers or lecturers, analyzing context, and utilizing resources such as dictionaries or glossaries. The correlation analysis between Vocabulary Learning Strategies and Vocabulary Size (r = 0.336) shows a moderate positive relationship, suggesting that these strategies play a role in enhancing vocabulary size. However, the findings also imply that other factors may contribute to vocabulary acquisition. Overall, this study highlights the importance of frequent reading and targeted vocabulary learning strategies for improving EFL students' vocabulary knowledge, providing valuable insights for more effective language instruction.